2016
DOI: 10.1016/j.jid.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein Contributes to the Development of Human Cutaneous Squamous Cell Carcinoma via Activation of RAS

Abstract: Cutaneous squamous cell carcinoma (cSCC) is one of the most common skin malignant tumors with an increasing incidence. Studies have shown that Yes-associated protein (YAP) participates in the development of a variety of tumors as an oncogene, but to our knowledge its role in cSCC has not been reported. In this study, we used immunohistochemistry to show that YAP expression was elevated in cSCC samples of different stages versus in normal skin and that it was well correlated with the progression of the disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 40 publications
5
63
0
Order By: Relevance
“…Furthermore, we found that YAP, like ACTL6A and p63, was required to sustain oncosphere formation by HNSCC cells (Figure 6E). In keeping with these data, a recent report demonstrates that activated YAP is required for in vivo tumorigenesis in cutaneous squamous cell carcinoma (Jia et al, 2016). Collectively, these data reveal that ACTL6A/p63 are required to induce and sustain YAP localization and activity in HNSCC.…”
Section: Resultssupporting
confidence: 57%
“…Furthermore, we found that YAP, like ACTL6A and p63, was required to sustain oncosphere formation by HNSCC cells (Figure 6E). In keeping with these data, a recent report demonstrates that activated YAP is required for in vivo tumorigenesis in cutaneous squamous cell carcinoma (Jia et al, 2016). Collectively, these data reveal that ACTL6A/p63 are required to induce and sustain YAP localization and activity in HNSCC.…”
Section: Resultssupporting
confidence: 57%
“…It is well documented that YAP and TAZ are required for normal epidermal development and hair growth in the mouse304142, and YAP and TAZ drive pro-tumorigenic signals in mouse and human cSCC3043. Nevertheless, there is ambiguity about YAP/TAZ function: YAP and TAZ are largely dispensible for homoeostasis of the IFE in adult mouse skin3042, and in cSCC both growth-promoting and growth-inhibiting functions have been documented4344.…”
Section: Resultsmentioning
confidence: 99%
“…In the skin, YAP is required for epidermal barrier formation, hair follicle development, and maintenance of the epidermal stem cell compartment (Zhang et al 2011;Barry and Camargo 2013;O'Neill 2015). Overexpression of YAP in transgenic mice promotes squamous cell carcinoma formation (Chan et al 2011;Jia et al 2016), whereas its knockdown inhibits cutaneous wound healing (Lee et al 2014), suggesting a central role in regulating proliferation. YAP and TAZ also respond to the rigidity of the extracellular matrix, cell geometry, cell density, cell polarity, and the status of the actin cytoskeleton.…”
Section: Mechanosensitive Signaling Pathways In the Control Of Desmosmentioning
confidence: 99%